Coping and Resilience Among Endurance Athletes During the COVID-19 Pandemic - Harman, Brian; Dessart, Grégory; Puke, Liene; Philippe, Roberta Antonini (Frontiers in Psychology, 2022)
COVID-19 lockdowns constrained the training opportunities of athletes resulting in physical and mental hardship. In this study, athletes involved in the outdoor endurance sports of running, cycling or swimming were recruited through Facebook groups and using online mailing lists. The final sample (n = 3551) consisted of 576 female respondents (16.2%), and 2975 male respondents (83.8%). The mean age of participants was 44.13 years (min=16, max=83, SD=9.84). An online survey was designed to measure variables relevant to athletes' mental health; resilience and emotion regulation strategies; mobility restrictions; training routines; personal involvement in endurance sports; age; gender; and country of residence. Overall, the results of our study indicate that during lockdown, decreases in training volume, lower lockdown-specific resilience and holding more negative perceptions about lockdown mobility restrictions (perceived strictness) all contributed to perceived barriers to training. In the analysis, athletes' relative observance of mobility restrictions was controlled for. Athletes exhibiting high personal commitment to their sports displayed: greater lockdown resilience, a greater use of adaptive coping strategies, and lower levels of perceived barriers to training.